Assessment of Rosemary (Rosmarinus officinalis L.) Extract as Antioxidant in Jelly Candies Made with Fructan Fibres and Stevia - Cristina Cedeño-Pinos; Magdalena Martínez-Tomé; María Antonia Murcia; María José Jordán; Sancho Bañón (MDPI AG, 2020)
Enrichment with rosemary antioxidants is proposed as a possible strategy to obtain healthier jelly candies. Two aqueous rosemary extracts (RE) containing 73.9 (RE74) and 145.6 (RE146) mg polyphenols per g fresh weight were assessed as antioxidants in jelly candies based on fructooligosaccharides, inulin and stevia. Up to 15 phenolic acids, flavonoids and diterpenes were determined in the extracts, with rosmarinic acid as the main active compound. Sensory tolerance, physical properties, rosmarinic acid recovery, polyphenol content, and antioxidant capacity were determined in jelly candies. The threshold of sensory detection was established at 0.26 g RE146/kg of raw candy, below which rosemary off-flavours were avoided without altering pH, brix, texture, CIELab colour, and consumer acceptance. Adding 0.26 g RE146 per kg increased (p < 0.001) polyphenol content from 197 to 411 µg GAE/g and the antioxidant capacity from 1.77 to 4.14 μmol Trolox/g. Rosemary polyphenols resulted in being resistant to cooking, acted as secondary antioxidants and showed good interaction with the other jelly ingredients. Aqueous extracts from rosemary distillation by-products can be incorporated at acceptable levels to jelly candy formulations leading to higher oxidative stability and an increased content of dietary polyphenols.